The Best that I Can Be: A Case for a Strengths-Based Approach during the First-Year Experience (Journal of Student Affairs in Africa, 2021)
More South African research is needed that examines the application of positive psychology to assist students in navigating the stressful first-year experience by identifying, developing and applying signature strengths. This article reports on a mixed methods study that investigated the efficacy of a strengths-based development programme presented to a sample of 55 first-year university students (mean age = 19.77, SD = 1.50, female = 60%). Quantitative data were collected in a pre- and post-intervention manner using the Personal Growth Initiative Scale, the Subjective Happiness Scale, the Satisfaction with Life Scale and the Strengths Use and Deficit Improvement Questionnaire. Qualitative data were collected in individual semi-structured interviews (n = 12, age range = 18-22). Significant changes between the pre- and post-test scores emerged when comparing the quantitative data. The qualitative analysis pointed to aspects that participants regarded as beneficial to the efficacy of the strengths-based programme. Collectively, the data integration suggested that the intervention had a positive impact on participants' sense of well-being and contributed to enhancing the first-year experience. Limitations and areas for further research conclude the discussion.
Keywords: first‑year experience; positive psychology; strengths use; well‑being